Emotional Intelligence and Organisational Citizenship Behaviour Using Structured Equation Modeling Approach - Jakulin Divya Mary, P.; Rajini, K. (International Journal of Engineering and Technology, 2018)
This paper focuses on deriving a model showing relationship between the Emotional Intelligence and Organisational Citizenship Behaviour.The model fits good for nurses who need to be emotionally intelligent and also show citizenship behavior towards the organization while dealing with patients, peer groups and supervisors.Study population were nurses working in a tertiary care hospital in Chennai. Sample size taken for the study was 100.Â Â Â